Analysis of Hemodynamic Changes after Administration of Mepivacaine HCL 3% with Prilocaine 3% Solution + Felypressin - Ehsan Aliabadi; Ahmad Homayoon; Hamidreza Eftekharian (Isfahan University of Medical Sciences, 2022)
With regards to the usage of local anesthetic drugs in hypertensive patients, this study is designed for comparing the effects of mepivacaine 3% and prilocaine 3% + felypressin in hemodynamic changes after inferior alveolar nerve block to help dental practitioner select anesthetic solutions for hypertensive patients considering their hemodynamic effects in order to provide patient safety.Materials & Methods:In this double blind clinical trial 32 patients were referred to oral and maxillofacial surgery department of Shiraz dentistry school in 2021 were divided into 2 groups with 16 patients in each group. In first group, inferior alveolar nerve block was accomplished by mepivacaine 3% and in the other group, prilocaine 3% and felypressin. Then systolic and diastolic blood pressure, heart rate and oxygen saturation were measured at 4 different time points consisting of before injection, immediately after injection, 10 minutes after injection and 30 minutes after tooth extraction. The data were analyzed by ANOVA and T-test (p value < 0.05).Results:There were no statistically significant differences in systolic blood pressure, diastolic blood pressure,heart rate and oxygen saturation changes between mepivacaine and prilocaine groups during all four sampling time points. But in each group, individually there were significant differences in systolic and diastolic blood pressure, heart rate and oxygen saturation in different times. In addition mepivacaine causes a significant increase in systolic blood pressure immediately after injection but in contrast prilocaine + felypressin didn't do so.Conclusion:We recommend prilocaine + felypressin in comparison with mepivacaine for local anesthesia in hypertensive patients